Analisis Pencemaran Udara Akibat Ulah Manusia di Majalaya - Elsan Septiani; Ageng Saepudin Kanda S (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims: to describe the composition and behavior of exhaust gases of motorized vehicles that can have an impact on human health. Based on the results of a theoretical study of various information that the main pollutants in motor vehicle exhaust gases are carbon monoxide (CO), hindrocarbon compounds, nitrogen oxides (NOx) and sulfur (SOx), and dust particulates including lead (PB). Chemical reactions in the atmosphere sometimes take place in a long and complex reaction chain, and produce an end product that can be more active or weaker than the original compound. Motor vehicle exhaust gases which have an impact on health are classified as follows; (1). Pollutants which mainly interfere with the respiratory tract. Included in this group are sulfur oxides, particulates, nitrogen oxides, ozone and other oxides, (2). Pollutants that cause systemic poisons, such as monoxide and lead / lead hydrocarbons, (3). Pollutants suspected of causing cancer such as hydrocarbons, (4). Conditions that interfere with comfort such as noise, street dust, etc. So the conclusion is that in anticipating the negative impacts caused by motor vehicle exhaust gases, the role of the government in setting several regulations and policies in the environmental field is needed, where every business or activity is prohibited from violating the quality standards and standard criteria of environmental damage set by government.